Therapeutic Comunication in Labour pain I Stage - Mundarti Mundarti; Tulus Puji Hastuti; Sri Widatiningsih (Poltekkes Kemenkes Semarang, 2013)
The research aims to identify the influence of therapeutic communication on pain intensity in stage I of birth within the area of Candimulyo Public Health Center. This was experimental study by using quasi-experimental design with control. Research instrument was a checklist of pain scale from 0-10. There were 62 repondents divided into 2 groups, 31 respondents for control group and 31 for case group. Wilcoxon test was conducted as analysis method. Before therepeutic communication was given, majority respondent experienced moderate pain (58%), afterwards they experienced mild pain 58%). In control group, moderate pain was experienced by 61.3% respondents and by the end of stage I the pain became severe (45.2%). Therapeutic communication had an impact on pain intensity in stage I of birth as proven by significant value of 0.0001.